Validation of Self-Statements during Public Speaking scale in Mexico - Moral de la Rubia, José (Consorcio de Universidades Mexicanas A.C., 2013)
The Self-Statements during Public Speaking (SSPS; Hofmann & DiBartolo, 2000) scale is an instrument that assesses cognitions in a public speaking situation, which commonly generates some degree of anxiety. The SSPS scale showed good psychometric properties in its original study with American samples in the same way as in its validation studies with Spanish samples. Despite its relevance, it was not adapted in the Mexican population. So the aims of this study were: to translate the SSPS scale into Mexican Spanish, to validate its structure of two correlated factors, to calculate its internal consistency, to describe its distribution, to contrast gender differences, and to observe the relationship of the SSPS scale with social desirability, a construct potentially linked to social anxiety. The SSPS scale and the Balanced Inventory of Desirable Responding (BIDR; Paulhus, 1998) were administered to a probability sample of university students stratified by gender. The structure of two correlated factors of positive and negative self-statements showed an adequate fit to data and invariance between both sexes by Generalized Least Squares. The Internal consistency was high; distribution was positively skewed. The correlation with social desirability was significant, especially with the self-deception factor. Men averaged higher, but the means of both genders were statistically equivalent when social desirability was controlled. We suggest using the SSPS scale in Mexico, controlling the social desirability bias.